Legal and administrative requirements and quality guidelines for agricultural and food exports to more developed CARICOM countries : a manual for CARICOM small and medium-sized enterprises (CDF BridgetownBB, 2011)
Identifies the types of information and documentation required by home countries to support export of food and agricultural products into the MDCs\n
Keywords: SMALL ENTERPRISES